ПОВЫШЕНИЕ ИНТЕРЕСА УЧАЩИХСЯ К ЛИТЕРАТУРЕ НА ОСНОВЕ АНАЛИЗА ХУДОЖЕСТВЕННЫХ ПРОИЗВЕДЕНИЙ - Алламбергенов, К.; Юсупов, К.А. (SCIENCE and SOCIETY, 2018)
The article is devoted to one of the actual problems today-ways of increasing student‘s interest to reading literary books on the basis of the literary- artistic analysis. As the material for the investigation were used the works of the famous Karakalpak writers, in the which the main character is Aydos biy-one of the political leaders of the Karakalpak people, who lived at the end of the XVIII-th and at the beginning of the XIX-th centuries.
Keywords: the process of the lesson; literature; specialist in literature; poetry; poem; character; creative work; style; method; writing; genres; training; analysis of works of art; didactic analysis